Changes in white matter functional networks across late adulthood - Li, Muwei; Gao, Yurui; Lawless, Richard D.; Xu, Lyuan; Zhao, Yu; Schilling, Kurt G.; Ding, Zhaohua; Anderson, Adam W.; Landman, Bennett A.; Gore, John C. (Frontiers in Aging Neuroscience, 2023)
The aging brain is characterized by decreases in not only neuronal density but also reductions in myelinated white matter (WM) fibers that provide the essential foundation for communication between cortical regions. Age-related degeneration of WM has been previously characterized by histopathology as well as T2 FLAIR and diffusion MRI. Recent studies have consistently shown that BOLD (blood oxygenation level dependent) effects in WM are robustly detectable, are weaker than in GM, they are modulated by neural activities, and thus represent a complementary window into the functional organization of the brain. However, there have been no previous systematic studies of whether or how WM BOLD signals vary with normal aging. We therefore performed a comprehensive quantification of WM BOLD signals across scales to evaluate their potential as indicators of functional changes that arise with aging. By using spatial independent component analysis (ICA) of BOLD signals acquired in a resting state, WM voxels were grouped into spatially distinct functional units. The spectral powers that reflect the intensities of BOLD signals were evaluated and found to be significantly affected by aging across more than half of the WM units. In addition, the functional connectivities (FCs) within and among those units were assessed and found to decrease significantly with aging. On a larger spatial scale, a graph was reconstructed based on the pair-wise connectivities among units, modeling the WM as a complex network and producing a set of graph-theoretical metrics. We observed a widespread reduction of those metrics, suggesting a decrease in the ability to exchange information between remote WM regions with aging. Our findings converge to support the notion that WM BOLD signals in specific regions, and their interactions with other regions, have the potential to serve as imaging markers of aging.